(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Primary Health Care (PHC) was the grass-root management approach to achieving the goal of “Health for all by the year 2000.” It is the first level care model of the National Health System where it is strategically positioned to be the first point of contact for the health challenges of individuals and families in the communities. Over the years, Nigeria has made several attempts to implementing PHC, however the fragmentation the health system is experiencing in the provision of health services and management of resources has caused a major setback. In an attempt to resolve these challenges facing the Nigerian health care system, the policy of bringing primary health care under one roof (PHCUOR) was adopted. This paper reviews the successes